First record of Fusarium concentricum (Hypocreales: Hypocreaceae) isolated from the moth Polychrosis cunninhamiacola (Lepidoptera: Tortricidae) as an entomopathogenic fungus. Issue 2 (14th March 2023) - Qiu, Hua-Long; Fox, Eduardo G P; Qin, Chang-Sheng; Yang, Hua; Tian, Long-Yan; Wang, De-Sen; Xu, Jin-Zhu
Abstract: Fusarium concentricum Nirenberg & O' Donnell (Ascomycota: Hypocreales) is a fungal species known to infect plants, but never reported as entomopathogenic. Polychrosis cunninhamiacola Liu et Pei (Lepidoptera: Tortricidae: Olethreutinae) is a major and widespread insect pest causing economic losses to cultivated Chinese fir Cunninghamia lanceolata (Lamb.) Hook. It is routinely controlled by extensive use of chemical insecticides, which is perceived as environmentally unsustainable. During March and April of 2019–2020, muscardine cadavers of larvae and pupae of P. cunninhamiacola infected with growing fungus were collected in a fir forest in northern Guangdong Province, China. Conidia were isolated and cultured on PDA medium, from which the fungal strain was identified as F. concentricum FCPC-L01 by morphology and by sequence alignment match with Tef-1α gene. Pathogenicity bioassays at the conidial concentration 1 × 10 7 revealed P. cunninhamiacola adults and Danaus chrysippus (L.) (Lepidoptera: Nymphalidae) larvae are sensitive to the fungal infection, but not the fire ant Solenopsis invicta Buren (Hymenoptera: Formicidae). We believe results indicate this fungal strain might be applicable against specific target insect pests. As this is the first record of a natural infection caused by F. concentricum in insects, we propose host specificity tests should be done to evaluate its potential as a biocontrol agent.